A checklist of the helminth parasites of sympatric rodents from two Mayan villages in Yucatán, México - Panti May, Jesús Alonso; Digiani, Maria Celina; Palomo Arjona, Eduardo Emir; Gurubel González, Yessica Margely; Navone, Graciela Teresa; Machain Williams, Carlos; Hernández Betancourt, Silvia F.; Robles, Maria del Rosario (Zootaxa)
In this survey, 19 species of helminths including Cestoda (Davaineidae, Hymenolepididae, and Taeniidae), Acanthocepha-la (Oligacanthorhynchidae), and Nematoda (Trichuridae, Ornithostrongylidae, Heligmonellidae, Oxyuridae, and Gongy-lonematidae) from Rattus rattus, Mus musculus, Sigmodon toltecus, Heteromys gaumeri, and Peromyscus yucatanicus in two Mayan villages in Yucatán, México, were recorded. Ten species of helminths were collected in both localities. The highest species richness was recorded in R. rattus from Xkalakdzonot (6 taxa). Twelve species are new records for Yucatán and two are registered for the first time in México. This survey constitutes the first checklist of helminth parasites in small rodents in the south-southeast of México. Fil: Panti May, Jesús Alonso. Universidad Autónoma de Yucatán; México Fil: Digiani, Maria Celina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División de Zoología Invertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Palomo Arjona, Eduardo Emir. Universidad Autónoma de Yucatán; México Fil: Gurubel González, Yessica Margely. Universidad Autónoma de Yucatán; México Fil: Navone, Graciela Teresa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Machain Williams, Carlos. Universidad Autónoma de Yucatán; México Fil: Hernández Betancourt, Silvia F. Universidad Autónoma de Yucatán; México Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina